Kontroversi Lafadz Allah: Analisis Lafadz Allah dalam Kristen di Malaysia - Fikril Jamil Bin Bidin (Lembaga Aneuk Muda Peduli Umat, Bekerjasama dengan Pusat Jurnal Universitas Islam Negeri Ar-Raniry Banda Aceh, 2022)
Kalima Allah is an issue after the court's decision rejected the application to use the Kalima Allah as a substitute for the words God or God in the Christian magazine Herald The Catholic Weekly in Malaysia into Malay. Various views from Muslims and non-Muslims say the law of using the word Allah is reasonable. This research uses library research, namely reading and researching and using books and media related to thesis discussion. The controversy over the word of Allah is more important than the discussion whether non-Muslims may use the word of Allah or not. These are two different issues. The request of the Christian party to use Allah's sentence was rejected by the court through a judicial decision on the grounds that it could cause confusion among fellow Muslims. But this has been interpreted by Muslims as a Christianization mission in Malaysia. Judging from the texts of the Koran, non-Muslims may pronounce Allah's words like Christianity. However, publications of The Herald in the English, Chinese and Indian versions do not change the word Allah and continue to use the same word, namely God or God in their languages. Only in the Malay language they want to use the word Allah. Abstrak Kalimah Allah adalah merupakan satu isu setelah keputusan kehakiman menolak permohonan penggunaan kalimah Allah sebagai pengganti perkataan God atau Tuhan dalam Herald The Catholic Weekly majalah Kristen di Malaysia ke dalam bahasa melayu. Berbagai macam pandangan dari muslim dan non muslim mengatakan hukum penggunaan kalimah Allah adalah wajar. Penelitian ini menggunakan riset perpustakaan (library research), yaitu membaca dan meneliti serta memakai buku-buku dan media yang berkaitan dengan pembahasan skripsi. Masalah kontroversi kalimah Allah lebih penting dari diskusi apakah non muslim boleh menggunakan kalimah Allah ataupun tidak. Ini adalah dua isu yang berbeda. Permohonan pihak Kristen untuk menggunakan kalimah Allah ditolak oleh pihak mahkamah melalui keputusan kehakiman dengan alasan karena bisa menimbulkan kekeliruan sesama muslim. Namun hal ini telah ditafsirkan umat Islam sebagai misi kristenisasi di Malaysia. Melihat dari nash Al-Quran, bahwa non muslim boleh menyebut kalimah Allah seperti agama Nasrani. Namun, terbitan The Herald dalam versi bahasa Inggris, Cina dan India tidak mengubah kata Allah dan tetap menggunakan kata yang sama yaitu God atau Tuhan dalam bahasa mereka. Hanya terbitan bahasa Melayu saja mereka ingin menggunakan kalimah Allah.